СУТНІСТЬ ПІЗНАВАЛЬНОЇ САМОСТІЙНОСТІ ЯК ВАЖЛИВОГО ПОКАЗНИКА ТВОРЧОЇ ОСОБИСТОСТІ (Педагогіка вищої та середньої школи, 2007)
The conditions of educational process, the conditions of its organization forms methods which help to debebop the Creative qualities of a person a covered in the article.